A mechanistic-empirical model for predicting top-down fatigue cracking in an asphalt pavement overlay. Issue 6 (18th August 2019) - Wu, Shenghua; Muhunthan, Balasingam
Abstract : Climate, pavement structure, traffic and material properties were identified and incorporated into a new mechanistic-empirical model to predict top-down cracking in an asphalt pavement overlay. The shear strain at the edge of the tyre was determined as a critical pavement structural response for initiating top-down cracking. The horizontal failure strain, dynamic modulus and shear strain at the edge of the tyre were incorporated in the model for characterising the fatigue life of asphalt pavements. The model was calibrated and verified using the data collected nationwide and is recommended to supplement the current models in the mechanistic-empirical pavement design guide (MEPDG). To mitigate top-down cracking in the asphalt pavement overlay, it is recommended to design an asphalt mix with relatively a higher horizontal failure strain value to reduce the shear strain response along the edges of the tyre.